Decisional impairments in cocaine addiction, reward bias, and cortical oscillation “unbalance” - Balconi M (Dove Medical Press, 2015)
Michela Balconi, Roberta Finocchiaro Research Unit in Affective and Social Neuroscience, Department of Psychology, Catholic University of the Sacred Heart, Milan, Italy Abstract: A vast amount of research has suggested that subjects with substance use disorder (SUD) might have difficulty making advantageous decisions that opt in favor of a longer-term, larger reward than an immediate, smaller reward. The current research explored the impact of reward bias and cortical frontal asymmetry (left lateralization effect) in SUD in response to a decisional task (Iowa Gambling Task). Fifty SUD participants and 40 controls (CG) were tested using the Iowa Gambling Task. Electrophysiology (electroencephalography) recording was performed during task execution. We measured left and right dorsolateral prefrontal cortex power activity. Behavioral responses (gain/loss options); frequency band modulation (asymmetry index) for delta, theta, alpha, and beta band; and cortical source localization (standardized low-resolution brain electromagnetic tomography) were considered. The SUD group opted in favor of the immediate reward option (loss) more frequently than the long-term option (gain) when compared to the CG. Secondly, SUD showed increased left-hemisphere activation in response to losing (with immediate reward) choices in comparison with the CG. The left hemispheric unbalance effect and the “reward bias” were adduced to explain the decisional impairment in SUD. Keywords: drug addiction, cortical brain oscillations, left lateralization effect, reward mechanism, Iowa Gambling Task